2010
DOI: 10.1590/s0004-27302010000800017
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive prolactinoma in a child related to germline mutation in the ARYL hydrocarbon receptor interacting protein (AIP) gene

Abstract: SUMMARYThe objective of this study was to describe a familial screening for AIP mutations in the context of aggressive prolactinoma in childhood. A 12-year-old boy, presented headaches and bilateral hemianopsia. He had adequate height and weight for his age (50 th percentile), Tanner stage G1 P1. His bone age was 10 years. Prolactin was 10.560 ng/mL (3-25), FSH and LH were undetectable, IGF-1, TSH, Free T4, ACTH, and cortisol were within normal ranges. MRI showed a pituitary macroadenoma, 5.3 X 4.0 X 3.5 cm wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Excluding the intronic variant of uncertain significance, AIP mutations were found in 1/3 FIPA patients and in 3/22 sporadic patients (13.6%). Such data are in agreement with AIP mutations associated with aggressive prolactinomas in FIPA and in young sporadic patients, with a male predominance (15,16,17). Further studies are necessary to better evaluate the prevalence of AIP mutations in sporadic-resistant prolactinomas.…”
Section: Discussionsupporting
confidence: 82%
“…Excluding the intronic variant of uncertain significance, AIP mutations were found in 1/3 FIPA patients and in 3/22 sporadic patients (13.6%). Such data are in agreement with AIP mutations associated with aggressive prolactinomas in FIPA and in young sporadic patients, with a male predominance (15,16,17). Further studies are necessary to better evaluate the prevalence of AIP mutations in sporadic-resistant prolactinomas.…”
Section: Discussionsupporting
confidence: 82%
“…At doses within the indicated range of about 2 mg per week, resistance to cabergoline treatment is rare. A recent multicenter study in 92 resistant prolactinomas reported that they comprised only about 3.4 % of prolactinomas overall, although this rate rose to 13 % in those with a genetic component to their tumorigenesis [21], such as AIP mutation [22,23]. Cabergoline has a long half-life and its potent D2 receptor affinity leads to a rapid and effective control of many prolactinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these patients were in isolated familial pituitary adenoma (FIPA) setting. Several studies have described the aggressive behavior of pituitary adenomas in younger ages that might be related to genetic syndromes, as MEN-1, AIP mutations, or X-Lag Syndrome [3941]. …”
Section: Discussionmentioning
confidence: 99%